Dietrich Bonhoeffers Psalmenauslegung in der Zeit des Dritten Reiches - Strohm, Christoph (Evangelische Theologie, 2017)
Bonhoeffer’s path »from a theologian to a Christian and contemporary« becomes vividly evident from his use of the Psalms. They are virtually irrelevant to his early works, but in the time of spiritual focussing in the first half of the 1930s, they come to buttress his individual piety as well as of his training of vicars. During his imprisonment the Psalms become an important means of communication and of sapiential insight. In addition, one may attribute a stimulating, intensifying effect on his development »from a theologian to a Christian and contemporary« to the Psalms. Evidence for this is the fact that, next to the Sermon on the Mount, the Psalms are the most important reference texts in the phase of Bonhoeffer’s spiritual focussing during the Kirchenkampf in the mid-1930s.
Gesehen am 12.06.2018
Keywords: Geschichte 1933-1944; Bibel / Psalmen; Bonhoeffer, Dietrich